The phytohormone abscisic acid enhances remyelination in mouse models of multiple sclerosis - Van Gaever, Femke; Mingneau, Fleur; Vanherle, Sam; Driege, Yasmine; Haegman, Mira; Van Wonterghem, Elien; Xie, Junhua; Vandenbroucke, Roosmarijn E.; Hendriks, Jerome J. A.; Beyaert, Rudi; Staal, Jens (Frontiers in Immunology, 2024)
IntroductionOver the past few decades, there has been a sudden rise in the incidence of Multiple Sclerosis (MS) in Western countries. However, current treatments often show limited efficacy in certain patients and are associated with adverse effects, which highlights the need for safer and more effective therapeutic approaches. Environmental factors, particularly dietary habits, have been observed to play a substantial role in the development of MS. In this study, we are the first to investigate the potential protective effect of the phytohormone abscisic acid (ABA) in MS. ABA, which is abundant in fruits such as figs, apricots and bilberries, is known to cross the blood-brain barrier and has demonstrated neuroprotective effects in conditions like depression and Alzheimer's disease.MethodsIn this study, we investigated whether ABA supplementation enhances remyelination in both ex vivo and in vivo mouse models.ResultsOur results indicated that ABA enhanced remyelination and that this enhanced remyelination is associated with increased lipid droplet load, reduced levels of degraded myelin, and a higher abundance of F4/80+ cells in the demyelinated brain of mice treated with ABA. In in vitro models, we further demonstrated that ABA treatment elevates lipid droplet formation by enhancing the phagocytic capacity of macrophages. Additionally, in a mouse model of microglial activation, we showed that ABA-treated mice maintain a less inflammatory microglial phenotype.ConclusionOur findings highlight a crucial role for macrophages and microglia in enabling ABA to enhance the remyelination process. Furthermore, ABA’s ability to improve remyelination together with its ability to reduce microglial activation, make ABA a promising candidate for modulating macrophage phenotype and reducing neuroinflammation in MS.